ATIM-41. PHASE II TRIAL OF A SURVIVIN VACCINE (SurVaxM) For Newly Diagnosed Glioblastoma. (5th November 2018) - Ahluwalia, Manmeet; Reardon, David; Abad, Ajay; Curry, William; Wong, Eric; Peereboom, David; Belal, Ahmed; Qiu, Jingxin; Mogensen, Kathleen; Schilero, Cathy; Casucci, Danielle; Mechtler, Laszlo; et al.
Abstract: BACKGROUND: Survivin is an anti-apoptotic protein that is highly expressed in glioblastoma (GBM). We conducted a single-arm, multi-center phase II trial in newly diagnosed GBM (nGBM) to determine 6-month progression-free survival (PFS-6), 12-month overall survival (OS-12) and immunologic response in patients treated with surgery, chemoradiation, adjuvant temozolomide (TMZ) and survivin-targeted immunization. METHODS: Patients with nGBM who hadwith HLA-A*02, -A*03, -A*11 and -A*24 haplotypes and, Karnofsky performance status ≥70 were included. Following craniotomy (3 residual contrast enhancement) and chemoradiation, patients received 4 prime-boost doses of SurVaxM (500 mcg) every 2 weeks, followed by adjuvant TMZ and maintenance SurVaxM every 12 weeks until progression. Immunogenicity of SurVaxM was assessed by measuring anti-survivin antibody levels and survivin-specific CD8+ T-cells using multimers. RESULTS: Sixty-three patients, median age 60 years (range, 20–82), including 38 males were treated. Survivin expression was detectable in all patients (1–40% ([median = 12%]) of tumor cells by immunohistochemistry). The vaccine was highly immunogenic and produced survivin-specific CD8+ T-cells and antibody (IgG) titers. The regimen was well-tolerated and immunogen-related adverse events were mild with no regimen limiting toxicity attributable to SurVaxM. PFS-6 was 96.7% (C.I. = 87.6%- 99.1%) and OS-12 was 94.2% (C.I. =83.0%-98.1%) as measured from diagnosis. In MGMT methylated, PFS6 of 96.9% (C.I. = 99.6% to 79.8%); OS12 of 98.1% (C.I. = 99.0% to 97.2%) and in unmethylated tumors, PFS6 of 96.6% (C.I. = 99.6% to 78%); OS12 of 88.9% (C.I. = 99% to 77.2%) was observed. Methylated patients with higher survivin levels had significantly better PFS-6 than those with low survivin levels (r = 0.4). CONCLUSIONS: SurVaxM is safe and a promising adjunct therapy in nGBM. Compared to historical matched controls, addition of SurVaxM improved PFS-6 and OS-12 in nGBM. Patients with poor prognostic factors (unmethylated MGMT, higher survivin levels) treated with SurVaxM achieved better survival than expected.